Treatment Duration And Family Support For Depression Symptoms In Pulmonary Tuberculosis Patients - Harits, Muhammad; Hartono, Hartono; Sumardino, Sumardino (Jurusan Keperawatan, Poltekkes Kemenkes Mataram, 2024)
TB control requires treatment for 6-8 months, the duration of this treatment can affect the level of depression symptoms in patients with pulmonary TB, the environment will also affect the emergence of depression symptoms in someone with pulmonary TB, the form of support that can be given is in the form of family support, this support is very important so that patients with pulmonary TB do not experience depression. Research Objectives. The purpose of this study was to determine the relationship between the duration of treatment and family support on the level of depression symptoms in patients with pulmonary tuberculosis. Research Methods Observational analytical design with a cross-sectional study approach. The sampling technique used was a non-probability sampling technique with a quota sampling method and 64 respondents were obtained. The instruments used were a family support questionnaire and a questionnaire on the level of depression symptoms. Data analysis used an ordinal logistic regression test with a p value <0.05. Research Results. The results of the simultaneous test of the relationship between the length of treatment and family support on the level of depression symptoms in patients with pulmonary TB at Surakarta General Hospital obtained a p-value of 0.000, then (p = 0.000 <0.05) meaning that the variables of length of treatment and family support together have an effect on the variable of the level of depression symptoms with a magnitude of the relationship of 47.5%. Conclusion. There is a significant relationship between the length of treatment and family support on the level of depression symptoms in patients with pulmonary TB at Surakarta General Hospital.